2015
DOI: 10.1002/gcc.22331
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent somatic loss of TNFRSF14 in classical Hodgkin lymphoma

Abstract: Investigation of the genetic lesions underlying classical Hodgkin lymphoma (CHL) has been challenging due to the rarity of Hodgkin and Reed-Sternberg (HRS) cells, the pathognomonic neoplastic cells of CHL. In an effort to catalog more comprehensively recurrent copy number alterations occurring during oncogenesis, we investigated somatic alterations involved in CHL using whole-genome sequencing-mediated copy number analysis of purified HRS cells. We performed low-coverage sequencing of small numbers of intact H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 53 publications
(111 reference statements)
1
17
0
1
Order By: Relevance
“…These data are of particular interest because we previously reported that HRS cell surface Figures 4A,D and 5). In addition to genetic alterations of MHC class I and class II antigen presentation pathway components, cHLs exhibited 1p36.32/TNFRSF14 copy loss as described 81 ( Figures 4A and 5). Of note, TNFRSF14 deficiency has been reported to disrupt B-and T-lymphocyte attenuator inhibitory T-cell signals and induce a tumor-supportive microenvironment in GC B-cell lymphomas ( Figure 5).…”
Section: -C A-g A-t C-a C-c C-g C-t G-a G-c G-g G-t T-a T-c T-g T-t Amentioning
confidence: 72%
See 1 more Smart Citation
“…These data are of particular interest because we previously reported that HRS cell surface Figures 4A,D and 5). In addition to genetic alterations of MHC class I and class II antigen presentation pathway components, cHLs exhibited 1p36.32/TNFRSF14 copy loss as described 81 ( Figures 4A and 5). Of note, TNFRSF14 deficiency has been reported to disrupt B-and T-lymphocyte attenuator inhibitory T-cell signals and induce a tumor-supportive microenvironment in GC B-cell lymphomas ( Figure 5).…”
Section: -C A-g A-t C-a C-c C-g C-t G-a G-c G-g G-t T-a T-c T-g T-t Amentioning
confidence: 72%
“…We identified 6 SCNAs (arm-level gain of 5p and 5q, focal loss of 1p36.32, 6p21.32, 6q23.3, and arm-level loss of 6q) that were recently described in DLBCL 26 as well as focal gain of 5p15.33 77,78 and focal loss of 6q12 79 that were reported in lung and prostate cancer, respectively. The focal region of 1p36.32 copy loss includes TNFRSF14 ( Figure 3A), 80,81 which is one of the most frequently mutated genes in GC-derived B-cell lymphomas. 26,82 Of interest, loss of TNFRSF14 and its encoded cell surface receptor HVEM leads to cell-autonomous B-cell activation and the development of GC B-cell lymphoma in vivo.…”
Section: Somatic Copy Number Alterations and Chromosomal Rearrangementsmentioning
confidence: 99%
“…Recently, recurrent losses of TNFRSF14 (herpesvirus entry mediator [HVEM]) have been described in cHL, 117 and previous studies in follicular lymphoma have provided evidence that loss of this receptor results not only in B-cell activation and proliferation but also in the induction of a tumor-supportive microenvironment. An elegant study conducted by Boice et al 118 showed that delivery of the HVEM ectodomain (soluble HVEM protein) by CD19 CAR T cells restored the tumor-suppressive effects of TNFRSF14 in a xenograft mouse model and that CAR T cells could be employed as "micropharmacies.…”
Section: Ruella Et Al 116 Developed Cd123 Car T Cells and Demonstratedmentioning
confidence: 99%
“…38 In this particular disease, highly sensitive techniques like dPCR and targeted NGS are essential to highlight low frequency mutations. High-throughput techniques such as low-coverage whole genome sequencing, 39 sequencing of circulating cfDNA 22 or targeted exome sequencing of isolated HRS cells 11 have recently helped to investigate genetic lesions underlying cHL, but sample sizes were very low. WES-based experiments of sorted Reed-Sternberg (RS) cells 11,40,41 recently identified new point mutations in cHL cases, including several mutations already reported in PMBL, such as CIITA, SOCS1, STAT6 and B2M mutations, as well as one case harboring the E571K XPO1 mutation, but this study was restricted to 10 cases, 11 with an insufficient median depth of sequencing (48X), which is potentially limiting for the discovery of genomic alterations.…”
Section: P=0000366 Diagnosis > Eotmentioning
confidence: 99%